Expression of the Wnt Receptor Frizzled-4 in the Human Enteric Nervous System of Infants. (30th November 2015) - Nothelfer, Katharina; Obermayr, Florian; Belz, Nadine; Reinartz, Ellen; Bareiss, Petra M.; Bühring, Hans-Jörg; Beschorner, Rudi; Just, Lothar
Abstract : The Wnt signalling pathway plays a crucial role in the development of the nervous system. This signalling cascade is initiated upon binding of the secreted Wnt ligand to a member of the family of frizzled receptors. In the present study, we analysed the presence of frizzled-4 in the enteric nervous system of human infants. Frizzled-4 could be identified by immunohistochemistry in a subpopulation of enteric neuronal and glial cells in the small and large intestine. Detection of frizzled-4 in the tunica muscularis by RT-PCR confirmed this receptor's expression on the mRNA level. Interestingly, we observed distinct cell populations that co-expressed frizzled-4 with the intermediate filament protein nestin and the neurotrophin receptorp75 NTR, which have been reported to be expressed in neural progenitor cells. Flow cytometry analysis revealed that 60% ofp75 NTR positive cells of the tunica muscularis were positive for frizzled-4. Additionally, in pathological samples of Hirschsprung's disease, the expression of this Wnt receptor correlated with the number of myenteric ganglion cells and decreased from normoganglionic to aganglionic areas of large intestine. The expression pattern of frizzled-4 indicates that this Wnt receptor could be involved in postnatal development and/or function of the enteric nervous system.